2015
DOI: 10.3168/jds.2014-8446
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of the effects of teat condition on the risk of new intramammary infections in dairy cows

Abstract: Machine milking-induced alterations of teat tissue may impair local defense mechanisms and increase the risk of new intramammary infections. The objective of the current study was to assess the influence of short-term and long-term alterations of teat tissue and infectious status of the udder quarter on the risk of naturally occurring new intramammary infections, inflammatory responses, and mastitis. Short-term and long-term changes in teat condition of right udder quarters of 135 cows of a commercial dairy fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“…No classical quarter level covariates (i.e., teat end score, papillomatosis, teat skin lacerations, and so on) were identified to be significant risk factors for speciesspecific CNS IMI in the present study. This is similar to the results of a German study in which no significant associations between teat end condition and new IMI caused by CNS or major mastitis pathogens were identified (Zoche-Golob et al, 2015). In contrast, associations of high teat end scores with a high infection rate of Staph.…”
Section: Variance Componentssupporting
confidence: 74%
See 1 more Smart Citation
“…No classical quarter level covariates (i.e., teat end score, papillomatosis, teat skin lacerations, and so on) were identified to be significant risk factors for speciesspecific CNS IMI in the present study. This is similar to the results of a German study in which no significant associations between teat end condition and new IMI caused by CNS or major mastitis pathogens were identified (Zoche-Golob et al, 2015). In contrast, associations of high teat end scores with a high infection rate of Staph.…”
Section: Variance Componentssupporting
confidence: 74%
“…In contrast, associations of high teat end scores with a high infection rate of Staph. aureus (Zadoks et al, 2001), high loads of Streptococcus uberis and Escherichia coli in the teat canals (Paduch et al, 2012;Zoche-Golob et al, 2015), and occurrence of clinical mastitis (Neijenhuis et al, 2001) were described by others. Recently, De Visscher et al (2016) found an increased risk for IMI with Staph, chromogenes, Staph.…”
Section: Variance Componentsmentioning
confidence: 99%
“…However, Guarin et al [10] could not find any association between hyperkeratosis and teat-skin load with environmental pathogens. Zoche-Golob et al [52] could not observe any variable describing teat condition on the risk of developing mastitis. According to our results, coliform bacterial load on teat ends increases as the percentage of cows with normal and healthy teat apices among all lactating cows per herd increases.…”
Section: Discussionmentioning
confidence: 88%
“…Scoring systems have also been developed for teat-end callosity or hyperkeratosis (Shearn & Hillerton, 1996). In a small study (135 cows), teat-end hyperkeratosis was not associated with the risk of mastitis, but a large study (1,667 cows) showed that severe hyperkeratosis is associated with increased risk of E. coli or S. uberis CM, and moderate hyperkeratosis with increased risk of E. coli CM (Breen, Green, & Bradley, 2009;Zoche-Golob et al, 2015). Bacterial loads of both organisms are higher in teat ends with hyperkeratosis than in those without, providing a plausible biological mechanism for the observed association (Paduch, Mohr, & Kr€ omker, 2012).…”
Section: Biosecuritymentioning
confidence: 99%